Influence of Waste Age on Landfill Leachate Quality - Lee, A.; Nikraz, Hamid; Hung, Y. (International Association of Computer Science and Information Technology (IACSIT), 2010)
The influence of waste age on the characteristic of leachate from a landfill site where yourng and mature waste cells were investigated over a period of six years to evaluate the impact of waste age on quality of leachate generated. Results of the study revealed that the leachate quality is affected by waste age due to its impacts to bacterial growth and chemical reaction in the waste mass of landfill.